Cultural anthropology : - Guest, Kenneth J. (W.W. Norton & Company, 2014)
Covering the essential concepts that drive cultural anthropology today, Ken Guest’s Cultural Anthropology: A Toolkit for a Global Age shows students that now, more than ever, global forces affect local culture and that the tools of cultural anthropology are essential to living in a global society. A “toolkit” approach encourages students to pay attention to big questions raised by anthropologists, offers study tools to remind readers what concepts are important, and shows them why it all matters in the real world.